DIGITAL TRANSFORMATION AND CULTURAL RESILIENCE IN KELANTAN’S TRADITIONAL MARKETS - Nazli, Nur Ain Amirah; Hapiz, Hana Yazmeen; Ghazali, Mohd Safwan (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME'S (AIJBES), 2025)
This paper explores the transformation of pasar tradisional (traditional markets) in Kelantan as traders increasingly adopt digital tools while sustaining their presence in physical marketplaces. Drawing on an anthropological perspective, the study examines how vendors integrate online banking, social media platforms, and e-commerce practices into daily business routines, yet continue to uphold the cultural and social value of face-to-face interactions. Rather than being replaced, the traditional market is reshaped by digital technologies, which expand customer networks, enhance financial management, and redefine entrepreneurial practices. Findings suggest that Kelantan’s pasar tradisional function as hybrid spaces where tradition and modernity coexist. Digital adoption does not undermine their cultural role but reinforces resilience by allowing traders to adapt to shifting consumer preferences and competitive pressures. These hybrid practices demonstrate how local communities negotiate continuity and change, ensuring that the market remains not only an economic arena but also a vital cultural and communal institution. This research offers insights into the adaptive strategies of small-scale traders in the digital era by placing Kelantan’s markets within wider discussions of digitalisation and cultural resilience. It highlights how local entrepreneurship reflects both innovation and heritage, offering implications for design, education, and policy on sustaining community-based economies in times of technological transition.